Heterozygous deletion of chromosome 17p renders prostate cancer vulnerable to inhibition of RNA polymerase II - Yujing Li (Nature Portfolio, 2018)
Heterozygous loss of chromosome 17p is a common genomic event in castration-resistant prostate cancers (CRPC). Here, the authors use CRISPR-based screen to identify RBX1 as a target gene for CRPC with 17p loss and targeting RBX1 sensitizes CRPC to the treatment of α-amanitin antibody conjugates.